Faith in Flux: Exploring Religion's Role in a Globalized World - Hakiki, Ach; Truna, Dody S.; Hannah, Neng (Hanifiya: Jurnal Studi Agama-Agama, 2025)
This article examines the dynamics of religion in the era of globalization based on perspectives outlined in the book Living Religions by Mary Pat Fisher and Robin Rinehart. Globalization has significantly influenced the practice and role of religion in modern society. On one hand, globalization creates opportunities for religious pluralism, cross-cultural dialogue, and the dissemination of universal values. On the other hand, it also presents challenges such as radicalization, interfaith conflicts, and the process of secularization. Using a descriptive-analytical approach, this article explores how religion functions as both an element of cultural and spiritual identity and a force for social transformation within an ever-changing global landscape. It also discusses the interaction between religion and politics, the role of religion in conflict resolution, and the importance of interfaith dialogue amidst technological advancements. The analysis reveals that religion remains relevant as a means of providing meaning and stability in the globalization era. Moreover, religion holds great potential to serve as a bridge for fostering harmony amidst diversity. Living Religions offers comprehensive insights into how religions adapt to global changes while maintaining the core values of each tradition.